Stressors and coping strategies of the Filipino sandwich generation - Suarez, Maria Carina Rose R.; Tongson, Excelsa C.; Tiu, Hasna Romaine L. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The purposes of this study were to identify the stressors faced by the Filipino sandwich generation as well as the strategies they use to control those stressors, which were analyzed through gender variables with consideration to the age of the dependents. Data was gathered through qualitative measures wherein 20 middle-aged members of the sandwich generation were interviewed. The data gathered showed that the common stressor experienced in relation to aging parents is dealing with their behaviors while stressors related to finances, and misbehaviors are the stressors related to children. Stress was also seen to come from other factors inside and outside the home. Meanwhile, coping strategies utilized involve the use technology, religion, social interaction, and engaging in personal time.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Stress (Psychology) -- Philippines; Sandwich generation -- Philippines